Preparation method and application of nickel honeycomb monolithic catalyst

By doping Co/CeOx oxide on the foam nickel substrate and combining low-temperature plasma technology, a nickel honeycomb integrated catalyst was developed, which solved the problems of low VOCs removal efficiency and poor stability of existing catalysts at low temperatures, and achieved efficient and stable VOCs removal effect, which was suitable for industrial applications.

CN119524864APending Publication Date: 2025-02-28CHANGZHOU UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411703153.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing catalysts have low efficiency and poor stability in removing VOCs at low temperatures, and the precious metal catalyst resources are scarce and costly, making it difficult to be suitable for industrial applications.

Method used

A nickel honeycomb integral catalyst is used. This catalyst is doped with a foamed nickel with high porosity as the substrate, and forms an active oxide layer with Co/CeOx oxide. Combined with low-temperature plasma technology, the activity and stability of the catalyst are enhanced.

Benefits of technology

At a temperature of ≥50°C and a plasma energy density of ≥158 J/L, the nickel honeycomb integral catalyst can achieve a 99% orthoxylene conversion and 83% COx selectivity, and maintain a high conversion rate of more than 15 hours under 50°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005153867060000011
    Figure HDA0005153867060000011
  • Figure HDA0005153867060000012
    Figure HDA0005153867060000012
Patent Text Reader

Abstract

The invention belongs to the field of removal of VOCs (Volatile Organic Compounds) through catalytic oxidation, and provides a preparation method and application of a nickel honeycomb monolithic catalyst. The nickel honeycomb monolithic catalyst is characterized in that the surface of foamed nickel is of a dense long fiber cluster sea urchin-shaped structure, fusiform rod-shaped structure substances are doped in the foamed nickel, and the preparation method comprises the following steps: S1, placing the foamed nickel in dilute nitric acid, carrying out ultrasonic washing, then carrying out repeated ultrasonic treatment in an acetone solution, and drying to obtain a pure foamed nickel carrier; s2, dissolving a cerium source and a cobalt source in a solvent, adding urea and a surfactant, immersing the foamed nickel, then transferring the foamed nickel into a reaction kettle for reaction, centrifuging and drying; and S3, placing in a muffle furnace, continuously calcining in an air atmosphere, and cooling to obtain the nickel honeycomb monolithic catalyst. Under the conditions that the temperature is 50 DEG C and the plasma discharge energy density is 158 J / L, 99% of o-xylene can be converted into COx.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic oxidation to remove VOCs, and specifically relates to a preparation method and application of a nickel honeycomb monolithic catalyst. Background Art

[0002] As one of the main air pollutants, VOCs form explosive mixtures with air and can cause combustion and explosion when exposed to open flames or high heat. Inhalation may cause irritation of the skin and mucous membranes and have an anesthetic effect on the central nervous system. Acute poisoning symptoms include coughing, tearing, conjunctival congestion, etc. Severe cases may cause hallucinations, delirium, and unconsciousness. At the same time, in the manufacturing and chemical industries, the emission of benzene series (including o-xylene) is extremely strict, and the maximum allowable emission concentration is 10mg / m 3 , the maximum allowable emission rate is 1.6kg / h. Therefore, the effective elimination of VOCs is a problem to be solved in many aspects such as industrial production.

[0003] The catalyst used in thermal catalysis needs to be at high temperature to initiate the catalytic reaction, which consumes a lot of energy and has poor economy and applicability. Therefore, scholars at home and abroad have proposed the idea of ​​using low-temperature plasma composite technology to degrade VOCs and put it into practice, achieving good results. However, the single use of low-temperature plasma to degrade VOCs still requires high energy consumption and produces more by-products, so a suitable catalyst is needed to make up for this defect. Low-temperature plasma synergistic catalytic technology combines the advantages of low-temperature plasma technology and catalytic oxidation technology. It has the characteristics of low energy consumption, high energy utilization, high purification rate and high selectivity. It is expected to be widely used in the field of harmless treatment of VOCs, but the development of low-temperature plasma synergistic catalysts is crucial.

[0004] At present, the commonly used catalysts are mainly precious metal catalysts and metal oxide catalysts (non-precious metals).

[0005] The document of Chinese patent CN 118874463A provides "a supported Pt2 cluster catalyst and its preparation method and application", which is characterized in that Pt is uniformly supported on a MnO2 carrier in the form of a Pt2 cluster. The supported Pt2 catalyst prepared by this invention is used in combination with low-temperature plasma technology, and has high removal efficiency for benzene-based organic volatiles, and the catalyst has a long life and can maintain high activity for a long time. The removal rate of o-xylene can reach 95.3% in 48 hours.

[0006] Although precious metals have shown excellent performance in the catalytic oxidation of VOCs, their resources are scarce, their prices are high, their preparation process is complex and they are prone to sintering, making them unsuitable for large-scale applications. In view of the challenges faced by precious metal catalysts in actual industrial applications, transition metal oxides and rare earth oxide catalysts have replaced precious metal catalysts and become one of the research focuses due to their advantages such as fast, effective, economical and applicable.

[0007] The document of Chinese patent CN 115400762A provides a "catalyst for synergistic low-temperature plasma catalysis of p-xylene", characterized in that the catalyst comprises manganese oxide, rare earth metal oxide and a carrier, wherein the manganese oxide and the rare earth metal oxide are both loaded on the carrier, wherein the active components of the catalyst are Mn, Co, La and Ce, and the p-xylene concentration is 30-200 mg / m 3 , the empty tower speed is 4500-5000h -1 , the discharge voltage is 20-40kV. The degradation rate can reach up to 90.3%.

[0008] Chinese patent CN 113385184A document provides "A Mn-Co-La composite catalyst for synergistic discharge plasma catalytic degradation of VOCs", characterized in that the composite catalyst includes active components and a dry gel carrier; the active components are Mn, Co and La, and in terms of atomic molar ratio, Mn:Co:La=0.5~2:0.5~2:1~2, and the size of the active components is 4-8nm; the active components are uniformly and orderly distributed in the dry gel carrier.

[0009] The document of Chinese patent CN113101923A provides "a Mn-Zr-La-Ce catalyst for degrading VOCs". The active components of the composite catalyst are Mn, Zr, La and Ce, and the specific surface area of ​​the composite catalyst is 100-300m 2 / g. The Mn-Zr-La-Ce composite catalyst has high catalytic activity and stability. The present invention also discloses a method for preparing a Mn-Zr-La-Ce catalyst for degrading VOCs. The preparation method is simple, green and pollution-free. The present invention also discloses the use of a Mn-Zr-La-Ce catalyst for degrading VOCs waste gas under the synergistic effect of low-temperature plasma to catalyze the degradation of ethyl acetate and meta-xylene, wherein the degradation rate of meta-xylene is relatively high and can reach 91.74% at 44kV.

[0010] The document of Chinese patent CN 1554480A provides "a cerium-based catalyst loaded with metal niobium and its preparation method and application". The present invention prepares a CeO2 catalyst carrier with a special structure, and adds a synergistic active component on the basis of the CeO2 catalyst carrier to improve the catalytic activity and inhibit chlorine poisoning. The catalyst uses the rare earth metal element niobium as the active component and broccoli-shaped nano cerium oxide as the carrier. The preparation process is simple and easy to operate. The metal elements used are low in cost and abundant in resources, which is conducive to large-scale use.

[0011] However, most transition metal catalysts exist in the form of powdered solids, which limits their use in industry, mainly due to the complex use environment that is prone to damage. Increased risk of secondary pollution, etc. Metal substrate monolithic catalysts refer to monolithic catalysts formed by coating active components on a metal substrate (FeCrAl metal mesh, aluminum sheet, titanium sheet, nickel foam, etc.) by methods such as impregnation, electroplating, and heat treatment deposition. Metal carriers have the advantages of good thermal conductivity, low specific heat capacity, strong corrosion resistance and impact resistance. Nickel foam is a porous mesh material with excellent properties such as large specific surface area, a large number of pores, good mechanical strength, light weight and flame retardancy, and has a three-dimensional network structure that is conducive to loading catalysts and increasing active sites. Due to its excellent properties, nickel foam is widely used. In the chemical catalysis industry, it can be used as a catalyst carrier.

[0012] Chinese patent CN 118513048A provides "a Co / MnO2 / MOF-derived in-situ grown on nickel foam" x The invention discloses a doped oxide catalyst and its preparation method and application, which belongs to the field of catalytic oxidation to remove CO. The invention first grows CoMn-MOF-74 in situ on nickel foam, and then obtains MOF-derived Co / MnO by high temperature calcination. x Doped oxide catalysts.

[0013] Chinese patent CN 112044448A provides "a VOCs catalytic combustion integral metal foam catalyst and its preparation and application". The catalyst uses foam nickel as a carrier and Pt or Pd as an active component, and the mass loading of the active component is 0.1% to 1%; the catalyst is prepared by an ion exchange method, and the reaction temperature is 20 to 90°C; the preparation method of the precious metal integral foam nickel catalyst of the present invention is simple and flexible, and it exhibits excellent activity in the catalytic combustion of VOCs, and has excellent water resistance, thermal shock resistance and very high stability. The complete conversion temperature can reach 280°C under the conditions of a toluene concentration of 2500ppm and an air velocity of 10000mL / (g·h).

[0014] The nickel foam-loaded catalyst showed good performance in the process of plasma catalytic degradation of VOCs, but it still had defects such as poor stability, short service life, and low selectivity in certain reactions. The above defects still need to be solved in practical applications. Summary of the invention

[0015] The present invention provides a nickel honeycomb monolithic catalyst, which has a plasma energy density of ≥158 J / L and a heat release rate of 865 mg / m 3 The conversion rate of o-xylene reached 99%, CO x The selectivity reached 83%, and the o-xylene conversion rate at 50°C remained above 97.5% within 15 hours.

[0016] Under the conditions of synergistic low-temperature plasma, the plasma and the rich porous metal structure of the nickel honeycomb monolithic catalyst carrier have a positive synergistic effect in enhancing the active particles and electron migration capabilities, as well as the redox performance. The cerium and cobalt active components in the catalyst have a relatively strong interaction during the discharge process, which can generate more chemically adsorbed oxygen species and activate more lattice oxygen, significantly promoting the oxidation ability of the catalyst and improving the activity level.

[0017] The nickel honeycomb monolithic catalyst of the present invention uses a foam nickel material with high porosity and good mass transfer effect as a substrate, and then dopes Co / CeO x Oxides form active oxidation layers, increasing the loading of active substances and increasing the adsorption sites of pollutants. As a unique metal substrate, nickel foam can enhance the internal potential between oxides and nickel honeycombs, promoting the activation of ozone into active oxygen species during the discharge process; under the plasma discharge state, its large interlayer space and mass transfer conductivity are conducive to the diffusion and mass transfer of molecules, allowing the intermediate products produced during the catalytic degradation of organic pollutants to be quickly desorbed and migrated, avoiding the deactivation of the catalyst, and thus achieving efficient removal of organic pollutants.

[0018] The method for preparing the above-mentioned nickel honeycomb monolithic catalyst comprises the following steps:

[0019] S1: The nickel foam carrier (NF) is immersed in dilute nitric acid and ultrasonically washed for 30 minutes. The acid-washed nickel foam is then immersed in an acetone solution and ultrasonically washed repeatedly. A pure nickel foam carrier can be obtained after drying.

[0020] S2: dissolving an appropriate amount of cerium source and cobalt source in a solvent, adding urea and a surfactant, immersing the nickel foam in the foam, and placing the foam in a reactor under high temperature and high pressure for several hours, centrifuging, and drying.

[0021] S3: Place in a muffle furnace and continue calcining in an air atmosphere to obtain a synergistic low-temperature plasma nickel honeycomb monolithic catalyst after cooling.

[0022] Furthermore, in step S2, the cerium source is a cerium salt such as cerium nitrate, cerium acetate, or a hydrate thereof, and the cobalt source is a cobalt salt such as cobalt nitrate, cobalt acetate, or a hydrate thereof;

[0023] Furthermore, the concentration of the nitric acid solution in step S1 is 3-5 mol / L, preferably 4 mol / L; the drying temperature is 80-100° C., and the drying time is 6-8 h, preferably 80° C., 8 h.

[0024] Furthermore, the molar ratio of Ce:Co of the cerium source and the cobalt source in step S2 is 1:0.75-1.75. The best ratio is 1:1.5.

[0025] Furthermore, in step S2, the molar ratio of the cerium source to urea is 7.85:5-10, preferably 7.85:8.

[0026] Furthermore, the surfactant in step S2 includes PEG-200, PEG-400, PEG-2000, hexadecyltrimethylammonium bromide, and thioacetic acid, preferably PEG-200; and the molar ratio of the cerium source to the surfactant is 7.85:1-4, preferably 7.85:4.

[0027] Furthermore, the solvent in step S2 is one or more of ethanol, diformamide, and deionized water.

[0028] Furthermore, the reaction temperature in step S2 is 140-180° C., and the reaction time is 12-18 hours, preferably 160° C., 18 hours.

[0029] Furthermore, the calcination temperature in step S3 is 550-750°C, the holding time is 3-5h, and the heating rate is 5-15°C / min. Preferably, the calcination temperature is 600°C, 4h, and the heating rate is 10°C / min.

[0030] The synergistic low-temperature plasma nickel honeycomb monolithic catalyst prepared by the above method.

[0031] The nickel honeycomb monolithic catalyst is used in conjunction with low-temperature plasma for catalytic oxidation of gases containing VOCs; the catalytic oxidation temperature is ≥50°C; and the energy density of the plasma is ≥158J / L.

[0032] Furthermore, the VOCs is o-xylene.

[0033] The beneficial effects of the present invention are:

[0034] The present invention combines the integral catalyst of the nickel honeycomb skeleton with plasma technology, ensuring that the catalyst has high overall strength and adaptability to complex environments, while using plasma synergistic technology to fully utilize the mass transfer advantages of the metal skeleton to greatly improve the catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 An electron microscope image of a synergistic low-temperature plasma nickel honeycomb monolithic catalyst provided in Example 1;

[0036] Figure 2 A transmission electron microscope image of a synergistic low-temperature plasma nickel honeycomb monolithic catalyst provided in Example 1;

[0037] Figure 3 An XRD spectrum of a synergistic low-temperature plasma nickel honeycomb monolithic catalyst provided in Example 1;

[0038] Figure 4 A graph showing the relationship between the o-xylene conversion rate and the energy density of a synergistic low-temperature plasma nickel honeycomb monolithic catalyst, CeO2-NF, Co3O4-NF and NF provided in Example 1;

[0039] Figure 5 This is a graph showing the sustained discharge stability experiment of a synergistic low-temperature plasma nickel honeycomb monolithic catalyst provided in Example 1. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0041] Example 1

[0042] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0043] 7.85mmol cerium nitrate and 11.78mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into the reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a synergistic low-temperature plasma nickel honeycomb monolithic catalyst (Co3O4 / CeO2-NF).

[0044] Example 2

[0045] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0046] 7.85mmol cerium nitrate and 5.88mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co 0.75 / Ce1-NF).

[0047] Example 3

[0048] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0049] 7.85mmol cerium nitrate and 7.85mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into the reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co1 / Ce1-NF).

[0050] Example 4

[0051] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0052] 7.85mmol cerium nitrate and 9.8mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co 1.25 / Ce1-NF).

[0053] Example 5

[0054] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0055] 7.85mmol cerium nitrate and 13.74mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co 1.75 / Ce1-NF).

[0056] Example 6

[0057] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0058] 7.85mmol of cerium nitrate was dissolved in 60ml of deionized water, and 8mmol of urea and 4mmol of surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then it was moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a synergistic low-temperature plasma nickel honeycomb monolithic catalyst (CeO2-NF).

[0059] Example 7

[0060] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0061] 11.78mmol of cobalt nitrate was dissolved in 60ml of deionized water, and 8mmol of urea and 4mmol of surfactant PEG-200 were added and stirred thoroughly, and then the treated nickel foam was added, and then it was moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a synergistic low-temperature plasma nickel honeycomb monolithic catalyst (Co3O4-NF).

[0062] Example 8

[0063] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0064] 7.85mmol cerium nitrate and 11.78mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-400 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co3O4 / CeO2-NF-400).

[0065] Example 9

[0066] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0067] 7.85mmol cerium nitrate and 11.78mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant PEG-2000 were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co3O4 / CeO2-NF-2000).

[0068] Example 10

[0069] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0070] 7.85mmol cerium nitrate and 11.78mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant hexadecyl trimethylammonium bromide (CTAB) were added and stirred thoroughly before adding the treated nickel foam, which was then transferred into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed two to three times with deionized water. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co3O4 / CeO2-NF-CTAB).

[0071] Embodiment 11

[0072] The processed nickel foam disc (1 cm in diameter, 4 mm in thickness) was immersed in 4 mol / L dilute nitric acid and ultrasonically washed for 30 min. The acid-washed nickel foam was then ultrasonically washed repeatedly in an acetone solution and dried at 80°C for 8 h to obtain a pure nickel foam carrier.

[0073] 7.85mmol cerium nitrate and 11.78mmol cobalt nitrate were dissolved in 60ml deionized water, and 8mmol urea and 4mmol surfactant thioacetic acid (TGA) were added and stirred thoroughly, and then the treated nickel foam was added, and then moved into a reactor and reacted at 160°C for 18h. The collected solution was poured into a centrifuge tube, placed in a high-speed centrifuge, and washed with deionized water two to three times. The reacted nickel foam was then calcined at 600°C in an air atmosphere for 4h to obtain a nickel honeycomb monolithic catalyst (Co3O4 / CeO2-NF-TGA).

[0074] Performance Testing:

[0075] The morphology and composition of Co3O4 / CeO2-NF catalyst were characterized.

[0076] 1. The image of Co3O4 / CeO2-NF catalyst taken by scanning electron microscope is shown in Figure 1 .

[0077] Analysis of results: On the Co3O4 / CeO2-NF catalyst, a cluster of dense long fibers, a sea urchin-like structure, can be observed on the surface of the nickel foam, interspersed with spindle-shaped rod-like structures. The filaments are about 3 microns long, the spindle-shaped rods are about 2 microns in diameter, and the length is about 8-15 microns. This multi-level hierarchical structure is likely to effectively increase the specific surface area of ​​the sample. During the discharge process of the DBD reactor, the honeycomb structure of nickel metal and a large amount of attached active substances greatly improve the performance of the sample in adsorption, catalytic oxidation, etc.

[0078] 2. The image of Co3O4 / CeO2-NF catalyst taken by transmission electron microscope is shown in Figure 2 .

[0079] Results analysis: The Co3O4 / CeO2-NF catalyst exhibits several lattice fringes with different spacings. Among them, the lattice fringes with a spacing of 0.299nm can correspond to the (111) crystal plane of CeO2, while the lattice fringes with a spacing of 0.458nm correspond to the (111) crystal plane of Co3O4.

[0080] 3. XRD analysis of Co3O4 / CeO2-NF catalyst Figure 3 . Analysis of results: The diffraction peaks of Co3O4 / CeO2-NF catalyst at 44.6°, 52.0° and 76.4° are attributed to the (111), (200) and (220) crystal planes of Ni, while the diffraction peaks at 28.6°, 33.1°, 47.5° and 56.3° are attributed to the (111), (200), (220) and (311) crystal planes of CeO2. The diffraction peaks at 36.7° and 68.6° are attributed to the (511) and (531) crystal planes of Co3O4, indicating that the phase components of the catalyst contain CeO2 and Co3O4 in addition to the substrate Ni. 4, It shows that the two elements of cerium and cobalt were successfully incorporated.

[0081] The catalytic performance of Co3O4 / CeO2-NF catalyst was characterized.

[0082] This experiment simulates the experimental system for evaluating the plasma catalytic degradation of o-xylene in air. The system consists of a pulse power supply, a dielectric barrier discharge (DBD) reactor, a voltage probe, a current probe, an oscilloscope, several gas mass flow meters, a sample injection pump, a vaporization chamber, several sections of heat preservation heating belts and a gas chromatograph. In simulated air (80% N2 and 20% O2), the o-xylene liquid is vaporized in the vaporization chamber to generate an o-xylene gas mixture (865 mg / m 3 ). The DBD reactor consists of a stainless steel rod (as a high voltage electrode), a stainless steel foil (as a ground electrode), and a quartz tube. The power supply is used to provide voltage pulses to the DBD reactor and generate gas discharges in the DBD reactor. The DBD reactor operates under normal temperature and pressure conditions. The waveform signals of the voltage probe and the current probe are digitized using an oscilloscope and used to calculate parameters such as discharge power, energy density, and efficiency.

[0083] The nickel honeycomb monolithic catalyst is arranged at the end of the electrode rod in the quartz tube (without destroying the structure of the foam nickel honeycomb metal skeleton). When the pollutant gas passes through, gas discharge is generated in the DBD reactor. We achieve different discharge powers by changing the voltage in steps (20-40kv), thereby achieving the oxidation of o-xylene.

[0084] 1. Table 1 shows the plasma energy density required for the complete oxidation of o-xylene at 50° C. using the monolithic catalyst or pure nickel foam (NF) prepared in Examples 1-9 as the catalyst and tested using the above method.

[0085] Analysis of results: After composited with Ce and Co oxides, the nickel foam had a lower plasma energy density for complete oxidation of o-xylene at the same temperature. Adjusting the surfactant and the Ce:Co molar ratio of the catalyst in the preparation of the catalyst affected the plasma energy density required for complete oxidation of o-xylene. The catalyst prepared under the conditions of Ce:Co molar ratio of 1:1.5 and PEG-200 as the surfactant had the lowest plasma energy density required for complete oxidation of o-xylene.

[0086] Table 1

[0087]

[0088] 2. The relationship between o-xylene conversion and energy density of Co3O4 / CeO2-NF, CeO2-NF, Co3O4-NF and NF catalysts is shown in Figure 4. Result analysis: Under the condition of 50℃, the conversion rate of o-xylene of Co3O4 / CeO2-NF reached 99% at an energy density of 158J / L, while the conversion rate of o-xylene of CeO2-NF and Co3O4-NF could reach 99% at an energy density of more than 200J / L. Reaction conditions: total flow rate 100mL / min, 20% O2, 80% N2, o-xylene concentration 865mg / m 3 The catalyst dosage is 5 particles (circular diameter 1 cm, thickness 4 mm), and the unit mass space velocity is about 20000 mL / (g·h).

[0089] 3. Stability test of Co3O4 / CeO2-NF at 50℃ and 158J / L Figure 5 Result analysis: The activity level of Co3O4 / CeO2-NF decreased by about 2% within 15h, but it could still be maintained above 97.5%. Reaction conditions: total flow rate 100mL / min, 20% O2, 80% N2, o-xylene concentration 865mg / m 3 The catalyst dosage is 5 particles (circular diameter 1 cm, thickness 4 mm), and the unit mass space velocity is about 20000 mL / (g·h).

[0090] Due to the low-temperature plasma nickel honeycomb monolithic catalyst provided by the present invention, 99% of o-xylene is converted into CO at a temperature of 50°C and an energy density of 158 J / L. x Therefore, the application provided by the present invention mainly includes the following three aspects:

[0091] (1) o-xylene is often used in the production of solvents, coatings, paints, cleaning agents and certain chemicals (such as phthalic acid, p-xylene, hydroquinone, etc.). In the chemical industry, contact with the vapor of o-xylene may cause harm. For the exhaust gas from pipelines and specific production workshops, it can be effectively treated into CO by plasma under low temperature conditions. x Lower emission standards.

[0092] (2) O-xylene is widely used as a solvent or diluent in the printing industry. Its working process may generate low-concentration pollutant gas indoors. The synergistic low-temperature plasma nickel honeycomb monolithic catalyst provided by the present invention can greatly reduce the generation of pollutant gas in the production process through discharge, and minimize the interference with the production process.

[0093] (3) In addition, for automobile exhaust (such as gasoline engines, diesel engines, etc.) and equipment cleaning, the VOCs produced can be reduced at the end of the emission by powering the original equipment.

[0094] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a nickel honeycomb monolithic catalyst, characterized in that: The following steps are involved: S1: soaking the nickel foam in dilute nitric acid, ultrasonically washing, then soaking the acid-washed nickel foam in acetone solution and repeatedly ultrasonicating, and drying to obtain a pure nickel foam carrier; S2: dissolving the cerium source and the cobalt source in a solvent, adding urea and a surfactant, immersing the nickel foam, and then transferring the nickel foam into a reactor for reaction, centrifuging, and drying; S3: placing in a muffle furnace, continuously calcining in an air atmosphere, and obtaining a nickel honeycomb monolithic catalyst after cooling.

2. The method for preparing the nickel honeycomb monolithic catalyst as claimed in claim 1, characterized in that: In step S1, the nickel foam is in the shape of a disc, and the diameter of the disc is 1 cm and the thickness is 4 mm; And / or, the concentration of the nitric acid solution is 3-5 mol / L.

3. The method for preparing the nickel honeycomb monolithic catalyst as claimed in claim 1, characterized in that: In step S2, the molar ratio of Ce:Co of the cerium source and the cobalt source is 1:0.75-1.

75.

4. The method for preparing the synergistic low-temperature plasma nickel honeycomb monolithic catalyst as claimed in claim 1, characterized in that: In step S2, the molar ratio of the cerium source to urea is 7.85:5-10; And / or, the solvent is one or more of ethanol, diformamide, and deionized water.

5. The method for preparing the nickel honeycomb monolithic catalyst as claimed in claim 1, characterized in that: The surfactant in step S2 includes PEG-200, PEG-400, PEG-2000, hexadecyltrimethylammonium bromide, and thioacetic acid; the molar ratio of the cerium source to the surfactant is 7.85:1-4.

6. The method for preparing the nickel honeycomb monolithic catalyst as claimed in claim 1, characterized in that: The reaction time in step S2 is 12-18 hours, and the reaction temperature is 140-180°C.

7. The method for preparing the nickel honeycomb monolithic catalyst as claimed in claim 1, characterized in that: In step S3, the calcination temperature is 550-750°C, the time is 3-5h, and the heating rate is 5-15°C / min.

8. A nickel honeycomb monolithic catalyst prepared by the method according to any one of claims 1 to 7.

9. Use of the nickel honeycomb monolithic catalyst as claimed in claim 8 in catalytic oxidation of VOCs, characterized in that: The nickel honeycomb monolithic catalyst cooperates with plasma to completely catalytically oxidize the gas containing VOCs; the catalytic oxidation temperature is ≥50°C; and the energy density of the plasma is ≥158J / L.

10. The use according to claim 9, characterized in that The VOCs is o-xylene.

Citation Information

Patent Citations

  • VOCs catalytic combustion monolithic metal foam catalyst and preparation and application thereof

    CN112044448A

  • Mn-Zr-La-Ce catalyst for degrading VOCs, and preparation method and low-temperature plasma concerted catalysis application of Mn-Zr-La-Ce catalyst

    CN113101923A

  • Mn-Co-La composite catalyst for catalytic degradation of VOCs in cooperation with discharge plasma as well as preparation method and application of Mn-Co-La composite catalyst

    CN113385184A

  • Catalyst for catalyzing p-xylene in cooperation with low-temperature plasma as well as preparation method and application of catalyst

    CN115400762A

  • MOF-derived Co / MnOx doped oxide catalyst grown on foamed nickel in situ and preparation method and application of Co / MnOx doped oxide catalyst

    CN118513048A